Investigation of the effect of anxiety disorder on time perception with zimbardo time perspective inventory - ULUCAN, KORKUT (My University, 2022)
Background:Linguists first coined the term anxiety in the 1600s to define a state of severe restlessness and worry. When we look at the Turkish dictionaries and printed sources, we see that the definition of anxiety is made simply as anxiety, fear, and worry. Anxiety; which we can describe as a mental and physical reaction, a defense strategy, against an event or fear. It will threaten the survival of the life; it is seen in two ways as situational anxiety and trait anxiety. Situational anxiety, as the name suggests, arises when faced with a threat or stress factor, while trait anxiety is an anxiety that occurs internally, independent of the event or situation.Aims and Objectives:For the continuity of one’s cognitive and behavioral abilities, not only anxiety but also the perception of time has a great place in the continuity of life. The findings that help us understand one’s time perspective are internal clock models and related mechanisms. This study aims to investigate the effect of anxiety on time perspective.Materials and Methods:To thisend, the Beck Anxiety Scale, the Zimbardo Time Perspective Inventory, and the demographic information form were used to collect data. Data were collected from a total of 168 participants, 44 females and 124 males.Results and Conclusion:When the findings are evaluated in general terms, there was a moderately negative relationship between anxiety and past positive perspective and a moderately positive relationship between past negative perspective. Based on this result, anxiety prevents a positive perception of the past; on the contrary, it can be said that it causes a negative perception of the past.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)